Non-pharmacological pain-relief interventions implemented by nurses in palliative care: scoping review protocol - Vicente, Ana (2022)
Aim: To identify and map the existing scientific evidence within the scope of non-pharmacological interventions implemented by nurses with the objective of providing pain relief to the people in a palliative situation. Method: This study followed the scoping review protocol based on the Joanna Briggs Institute methodology. In regard to the research strategy and identification of studies, the following electronic databases were consulted: MEDLINE (via Pubmed), CINAHL Complete (via EBSCOhost), Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews, Scielo, JBI Library of Systematic Reviews, and Scopus. In addition, the search for unpublished studies included the Scientific Repository for Open Access of Portugal (RCAAP) and OpenGrey. The research strategy included all the articles published in Portuguese, Spanish and English in the last 5 years. Results: Following the main objective, focus and research question, the results will be presented in a narrative format, using tables. The mapping of the non-pharmacological interventions implemented by nurses focused on pain relief will contribute to the dissemination of the available evidence. Conclusion: It is expected that the present scoping review will contribute to the critical analysis of non-pharmacological interventions implemented by nurses in this area given the potential impact of these on pain relief and the quality of care provided.